THE WAR OF DIGITAL ERA: ROLE OF AI IN IRAN-ISRAEL CONFRONTATION (Contemporary Journal of Social Science Review, 2025)
The use of artificial intelligence has transformed military strategy and national interest preservation due to its rapid integration and improvement into valuable supplies. A key aspect of recent developments is the growing reliance on Artificial Intelligence (AI) and integrated algorithms in shaping modern military strategy. This study used the descriptive research method to explore the Iran-Israel war and the uses of AI technology. Israel employs Artificial intelligence and its integrated algorithms in its military as a military strategy to predict aerial targeting and utilize drone systems. Israel has a technological edge in the military systems applied in artificial intelligence, while having technological edge of military combat systems. Iran, despite economic constraints, has developed strong asymmetric capabilities through cyber warfare, UAVs, and AI-enabled proxy networks. This evolution has turned their longstanding conflict into a technologically advanced confrontation defined by speed, automation, and increasing unpredictability.